2020
DOI: 10.3389/fonc.2020.582686
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Eltrombopag and Romiplostim in Myelodysplastic Syndromes: A Systematic Review and Meta-Analysis

Abstract: Background and AimMany studies indicated that eltrombopag and romiplostim could improve hematopoietic function in patients with myelodysplastic syndromes (MDS), but their toxicity and efficacy were not known. This meta-analysis aimed to investigate the safety and efficacy of eltrombopag and romiplostim in MDS.MethodsA full-scale search strategy was used to search relevant published studies in PubMed, Embase, Web of Science, ClinicalTrials.gov and the Cochrane Library until January 2020 using a random-effects m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…We observed disease progression in 17% of the patients (including AML transformation in four), figures similar to those observed by Oliva et al 11 in both ELT-and placebo-treated patients, and concordant with the 'natural' evolution of LR-MDS. 1 In a recent meta-analysis in MDS, 30 a potential increased risk of disease progression with TPO mimetics was likewise not confirmed. The risk of progression with ELT was found to be higher in CMML, but in a series where many patients initially had an excess of marrow blasts.…”
Section: Discussionmentioning
confidence: 97%
“…We observed disease progression in 17% of the patients (including AML transformation in four), figures similar to those observed by Oliva et al 11 in both ELT-and placebo-treated patients, and concordant with the 'natural' evolution of LR-MDS. 1 In a recent meta-analysis in MDS, 30 a potential increased risk of disease progression with TPO mimetics was likewise not confirmed. The risk of progression with ELT was found to be higher in CMML, but in a series where many patients initially had an excess of marrow blasts.…”
Section: Discussionmentioning
confidence: 97%
“…Recent data have suggested activity for the TPO-RAs lusutrombopag and eltrombopag for patients with CIT. [10][11][12] Lusutrombopag is currently FDA-approved for management of thrombocytopenia in patients with chronic liver disease who are scheduled to undergo a medical or dental procedure, and eltrombopag is approved for patients with chronic immune thrombocytopenia or severe aplastic anemia. The efficacy of lusutrombopag was assessed in an integrated analysis of data from 2 phase III trials that compared lusutrombopag versus placebo in 270 patients with chronic liver disease and hepatocellular carcinoma.…”
Section: Additional Tpo-ra Agentsmentioning
confidence: 99%
“…A large and recent meta-analysis investigated the results of 8 randomized studies including 707 patients with different forms of myelodysplastic syndrome (MDS), who are at high risk of leukemic transformation. 57 The authors concluded that neither romiplostim nor eltrombopag promoted progression to leukemia (Risk Ratio: 1.08 and 1.12, respectively).…”
Section: Treatments To Stably Increase Platelet Count In Subjects Wit...mentioning
confidence: 99%